Les trois institutions oratoires à l'usage de Henri III : un compendium des traditions latine, hellénistique et humaniste - La Charité, Claude (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (CRRS, Victoria University, 2008)
The literary tradition has preserved three Artes Rhetoricae written for the last of the Valois kings, who reigned in France under the name of Henry III from 1574 to 1589. These three texts are Jacques Davy Du Perron's Avant-discours de rhetorique, ou Traitté de l'eloquence, Jacques Amyot's Projet de l'eloquence royale, and Germain Forget's Rhetorique françoise faicte particulierement pour le roy Henry 3. All three very likely originated as academic speeches pronounced at the Louvre, in the presence of Henry III, in the final sessions of the Palace Academy during the summer of 1579. This article offers a re-reading of the three treatises in order to situate them in the history of rhetoric. It aims to show how each author collects and presents teachings of the principal rhetorical traditions. Thus, Du Perron, inspired mainly by Quintilian and Cicero, proposes a kind of abridged version of the rhetorical thought of Latin Antiquity. Amyot, for his part, puts forth a synthesis of ancient Greek rhetorical theory starting with Plutarch, Dyonisius of Halicarnassus and Demetrius of Phalerus. Germain Forget provides an account of Renaissance innovations, by adopting the nomenclature of Peter Ramus under the rubric of elocutio. The objective of this essay is to shed light on the complementary nature of the three treatises, as well as to suggest a probable order in which they were presented to the King, following a logical gradation from the most general to the most specific.